Challenges and Opportunities in the Future Applications of IoT Technology - Tarek M. Attia (International Telecommunications Society (ITS), 2019)
The advent of internet of things (IoT) has influenced and revolutionized the information systems and computing technologies. A computing concept where physical objects used in daily life, will identify themselves by getting connected to the internet is called IoT. Physical objects embedded with electronic, radio-frequency identification, software, sensors, actuators and smart objects converge with the internet to accumulate and share data in IoT. IoT is expected to bring in extreme changes and solutions to most of the daily problems in the real world. Thus, IoT provides connectivity for everyone and everything at any time. The IoT embeds some intelligence in Internet connected objects to communicate, exchange information, take decisions, invoke actions and provide amazing services. It has an imperative economic and societal impact for the future construction of information, network, and communication technology. In the upcoming years, the IoT is expected to bridge various technologies to enable new applications by connecting physical objects together to support the intelligent decision making. As the most cost-effective and performant source of positioning and timing information in outdoor environments, the global navigation satellite systems(GNSS) has become an essential element of major contemporary technology developments notably including the IoT, Big Data, Smart Cities and Multimodal Logistics. By 2020, there will be more than 20 billion interconnected IoT devices, and its market size may reach 1.5 trillion. Projections for the impact of IoT on the Internet and economy are impressive, with some anticipating as many as 100 billion connected IoT devices and a global economic impact of more than 11 trillion by 2025. Regulators can play a role in encouraging the development and adoption of the IoT, by preventing abuse of market dominance, protecting users and protecting Internet networks while promoting efficient markets and the public interest. Regulators can consider and identify some measures to foster development of the IoT. Encourage development of LTE-A and 5G wireless networks, and keep need for IoT-specific spectrum under review. Universal IPv6 adoption by governments in their own services and procurements, and other incentives for private sector adoption. Increasing interoperability through competition law and give users a right to easy access to personal data. Support global standardization and deployment of remotely provisioned SIMs for greater machine to machine competition. Particular attention will be needed from regulators to IoT privacy and security issues, which are key to encouraging public trust in and adoption of the technology. This paper focuses specifically on the essential technologies that enable the implementation of IoT and the general layered architecture of IoT, the market of IoT and GNSS technologies and their impact of the world economy, application domain of IoT and finally the Policy and regulatory implications and best practices.
Keywords: 330; Internet of Things(IoT); Global Navigation Satellite Systems(GNSS); Applications; Marketing; Policy and Regulation